2017
DOI: 10.1038/srep44749
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of nighttime sleep duration in one-month-old infants on alterations in natural and artificial photoperiod

Abstract: Human sleep–wake cycles are entrained by both natural and artificial light–dark cycles. However, little is known regarding when and how the photoperiod changes entrain the biological clock after conception. To investigate the dependence of sleep patterns in young infants on the natural and artificial light–dark cycles, 1,302 pairs of one-month-old infants and their mothers were asked to answer a questionnaire. Birth in spring, longer daytime sleep duration, early/regular light-off times, and longer maternal ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…Although no significant risk factors were found in 8‐month‐old infants, the photoperiod during the first 3 months was related to slower development of sleep–wake rhythm at the age of 3 months. This corresponds with findings in animal and infant studies (Brooks & Canal, ; Iwata et al., ). Exposure to a long photoperiod leads to a phase delay in circadian rhythms and thus also affects the sleep–wake cycle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although no significant risk factors were found in 8‐month‐old infants, the photoperiod during the first 3 months was related to slower development of sleep–wake rhythm at the age of 3 months. This corresponds with findings in animal and infant studies (Brooks & Canal, ; Iwata et al., ). Exposure to a long photoperiod leads to a phase delay in circadian rhythms and thus also affects the sleep–wake cycle.…”
Section: Discussionsupporting
confidence: 91%
“…Animal studies provide evidence that the postnatal light environment affects the development of circadian rhythms (Brooks & Canal, ). Alternations in natural and artificial photoperiods have also been related to infants’ night‐time sleep duration (Iwata et al., ). Moreover, the development of the sleep–wake rhythm might be related to feeding and social cues (McGraw, Hoffmann, Harker, & Herman, ; Mirmiran, Baldwin, & Ariagno, ).…”
Section: Introductionmentioning
confidence: 99%
“…Infant sleep quality and development can be modulated by a number of biopsychosocial factors [23]. These factors include inherited child's characteristics, such as temperament [24] or chronotype [19], perinatal characteristics such as season of birth [25] or photoperiod [26], and environmental characteristics such as parental stress [27]. Following this line of research, our recent study reported that some maternal risk factors during pregnancy are related to infants' sleep difficulties at three months of age [28].…”
Section: Introductionmentioning
confidence: 97%
“…Data are presented as mean ± standard deviation, number (%) or median (interquartile range). Clinical backgrounds of the study population have been published previously 10 . Of the questionnaires collected from 1,302 participating mothers, data from 31 mothers were excluded due to excessive missing data.…”
Section: Resultsmentioning
confidence: 99%